The Contribution of the Flipped Classroom to the Development of Students' Language and Communication Skills. Action Research in the Modern Greek Language Course - Κούρτη, Στυλιανή; Σιδηροπούλου, Μαρέττα (Education Sciences, 2021)
The purpose of this paper is to research the effect of the Flipped Classroom on the utilization of teaching time, in order to implement student-centered activities that enhance the language and communication skills of students. In order to answer the research questions, the method of action research was used and educational material was designed, which was posted on the educational platform e-me, while collaborative activities relating to the comprehension and formation of oral and written speech were developed in the classroom. The results indicated that this model clears up most of the teaching time, while the performance of the students experimental group displays an upward trend during the intervention in the comprehension and formation of oral and written speech. From the analysis of the results, it is concluded that the application of the Flipped Classroom model contributes to the utilization of teaching time for the implementation of student-centered activities that enhance the language and communication skills of students, which is also the purpose of the course of Modern Greek Language in junior High School.